A study on contraceptive knowledge, attitudes and practices among women in the reproductive age group - Shukla, Mansi; Fonseca, Mallika; Deshmukh, Prasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India, with one of the world’s fastest growing populations, is a nation very much in need of contraceptive counselling. To assess the knowledge and attitude regarding family planning methods and contraceptive practices among women of reproductive age group. Methods: A cross-sectional study was performed in which 547 women in the reproductive age group i.e., 15-45 years, attending a tertiary care hospital in Mumbai were interviewed with predesigned validated questionnaire. A total of 547 women were interviewed using a semi-structured questionnaire from January 2016 to December 2016. The proforma included details such as socio-demographic features, questions related to knowledge, attitude and practices (KAP) regarding contraceptive use. Results: Out of 547 women interviewed, 498 (i.e. 91%) had displayed an awareness of family planning methods (permanent/temporary). Out of these 498 women, about 78% had procured the information from family and friends. 13% got their information through mass media. Only 9% of women had been counselled in detail by health personnel about the various contraceptive options available. Out of 547 women interviewed, 342 (62.5%) were using contraception. More than a third of these women (26.8%), resort to barrier contraception as a contraceptive method of choice for spacing and to prevent an unwanted pregnancy. Only 17% women used OC Pills as a contraceptive method though 66% women knew about them. Though 59.4% of the women knew about IUCDs only 3.5% were actually using IUCD. Most of the women were in the younger age group of 21-30years (62%) and already had one or two children. Conclusions: Ignorance regarding use and side effects various contraceptive methods is the reason for inadequate practice of family planning methods. There should be emphasis on focused awareness programs, based on bridging the knowledge gaps among the women in reproductive age group.